2017
DOI: 10.15171/jrip.2017.45
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D, parathyroid hormone and inflammatory markers in urolithiasis patients

Abstract: Implication for health policy/practice/research/medical education:As urolithiasis patients are at a constant inflammatory insult caused by the calculi, the levels of inflammatory markers can be used to monitor the success of treatment. Vitamin D and anti-inflammatory agents may be used in the management of nephrolithiasis patients. Please cite this paper as: Introduction:Hypercalciuria plays an important role in the pathogenesis of renal calculi. The role of vitamin D, parathyroid hormone (PTH), inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…However, more studies should be developed to clarify the function of PTH in ameloblasts and odontoblasts and its impact on dental caries susceptibility and progression. Although PTH serum levels have been investigated in a variety of conditions (14)(15)(16)(17), the relationship between PTH serum levels and dental caries is not clarified yet. While Gyll et al (25) did not observe differences in PTH serum levels between caries and caries-free children, on the other hand, Schroth et al (26) and Deane et al (27) showed an increase in PTH levels in children with Severe Early Childhood Caries, apart from observing a decrease of calcium and 1,25-dihydroxy vitamin D levels in these children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more studies should be developed to clarify the function of PTH in ameloblasts and odontoblasts and its impact on dental caries susceptibility and progression. Although PTH serum levels have been investigated in a variety of conditions (14)(15)(16)(17), the relationship between PTH serum levels and dental caries is not clarified yet. While Gyll et al (25) did not observe differences in PTH serum levels between caries and caries-free children, on the other hand, Schroth et al (26) and Deane et al (27) showed an increase in PTH levels in children with Severe Early Childhood Caries, apart from observing a decrease of calcium and 1,25-dihydroxy vitamin D levels in these children.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that changes in PTH levels can unbalance the levels of inflammatory mediators and un-regulate the host's response to dental caries. In fact, by a process not fully understood, the serum levels of some pro-inflammatory proteins, like interleukin-6 (IL-6) and IL-1β, are greater in patients diagnosed with primary or secondary hyperparathyroidism, a condition characterized by hypersecretion of PTH (17,28,29). Interestingly, IL-6 and IL-1β were already previously associated with dental caries (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hemodialysis there is chronic inflammation and PTH is also usually high unless treated. [23]. However there are also a few recent papers that have shown association of PTH with resolution of inflammation and healing in several contexts e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There are number of studies reporting the association between increased in ammatory markers and urolithiasis, however the pathophysiology of urolithiasis remains unclear [2][3][4]. In ammation plays a crucial role in the initial stage and the progression of urinary stones.…”
Section: Introductionmentioning
confidence: 99%